Interpersonal Psychotherapy vs. Treatment as Usual for Major Depression Related to Work Stress: A Pilot Randomized Controlled Study - Schramm, Elisabeth; Mack, Simon; Thiel, Nicola; Jenkner, Carolin; Elsaesser, Moritz; Fangmeier, Thomas (Frontiers in Psychiatry, 2020)
Background: Depressive disorders are among the leading causes of sick leave and long-term work incapacity in most modern countries. Work related stress is described by patients as the most common context of depression. It is vital to know what types of treatments are effective in improving work related problems and occupational health. However, there is only limited evidence on work-focused interventions. Methods: The aim of our study was to evaluate the feasibility and generate first data on the effectiveness of Interpersonal Psychotherapy (IPT) adapted as a group program to focus on the work context (W-IPT). In total, 28 outpatients (22 women; M = 49.8 years old) with Major Depressive Disorder related to work stress were randomized to 8 weekly group sessions of W-IPT or to treatment as usual (TAU; guideline oriented treatment). Primary endpoint was the Hamilton Rating Scale for Depression (HRSD-24) score. Key secondary endpoints were, among others, Beck Depression Inventory (BDI-II), Work Ability Index (WAI), Return to Work Attitude (RTW-SE), and the Effort-Reward-Imbalance (ERI). In addition, we evaluated the participants' overall satisfaction with the W-IPT program by two items. A follow-up assessment was conducted 3 months after end of acute treatment. Results: W-IPT was significantly more effective than TAU in reducing clinician-assessed depressive symptoms at follow-up (HRSD-24 W-IPT/TAU: M = 6.6/12.0, SE: 1.46/2.17, t(df = 1) = −2.24, p = 0.035, d = 0.79) and self-assessed depression (BDI-II W-IPT/TAU post-treatment: M = 8.8/18.8, SE: 1.69/2.70, t(df = 1) = −3.82, p = 0.001, d = 1.28; follow-up: M = 8.8/16.1, SE: 1.62/2.26, t(df = 1) = −2.62, p = 0.015, d = 0.99). Furthermore, W-IPT was superior in improving work-ability (WAI), return-to-work attitude (RTW-SE), and the effort-reward-ratio (ERI). No dropouts were observed in both groups. The vast majority (89 percent) of participants in the W-IPT condition were “very satisfied” with the program, although wishing for a greater number of sessions (75 percent). Conclusions: A work-focused IPT program for the treatment of depression associated to work stress was feasible and highly acceptable. W-IPT turned out to be more effective than standard treatment in reducing depression and work-related problems. However, further evidence in a multicenter trial extending this pilot study is necessary.